2012
DOI: 10.1167/12.10.16
|View full text |Cite
|
Sign up to set email alerts
|

Binocular rivalry of spiral and linear moving random dot patterns in human observers

Abstract: Binocular rivalry describes the alternating perception of two competing monocular images. It is hypothesized to arise at multiple levels of the visual pathway due to competition between neuronal populations representing the displayed images. We tested whether an enhanced neural representation of expanding motion yields a bias over other spiral motion (i.e., contraction and rotation) and linear motion stimuli during binocular rivalry. We presented random dot patterns of different motion types (i.e., linear and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 94 publications
1
28
0
Order By: Relevance
“…This realization led us to analyze EXP and CON dominance durations measured during the sitting condition in Experiments 2 and 3, where one's own actions do not imply self-production of optic flow on the retina. In that combined data set, EXP dominance durations were significantly longer than were CON durations (3.72 vs 3.175 s, T-test P = .003, ks-test P = .00006), mirroring earlier findings (Conrad et al, 2013;Malek et al, 2012; but see Parker & Alais, 2007). So, perhaps walking vetoes the sense of looming and pending collision signified by centrifugal radial motion viewed by a stationary observer.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…This realization led us to analyze EXP and CON dominance durations measured during the sitting condition in Experiments 2 and 3, where one's own actions do not imply self-production of optic flow on the retina. In that combined data set, EXP dominance durations were significantly longer than were CON durations (3.72 vs 3.175 s, T-test P = .003, ks-test P = .00006), mirroring earlier findings (Conrad et al, 2013;Malek et al, 2012; but see Parker & Alais, 2007). So, perhaps walking vetoes the sense of looming and pending collision signified by centrifugal radial motion viewed by a stationary observer.…”
Section: Discussionsupporting
confidence: 71%
“…3a), and they are accompanied by intervening periods of mixtures. We would note, too, that other studies of motion-induced rivalry have successfully used RDCs of the sort we employed (Blake et al, 1985(Blake et al, , 1998Chen et al, 2001;Parker & Alais, 2007;Malek et al, 2012;Holten et al, 2015). We are thus satisfied that the stimuli we employed are sufficient to generate robust binocular rivalry.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Another study has showed that counter phase gratings with equal motion components in both directions appeared to drift foveofugally rather than foveopetally (Georgeson & Harris, 1978). Also, longer dominance durations for expanding optic flow compared with contracting optic flow are reported during binocular rivalry (Malek et al, 2012;Parker & Alais, 2007). However, this apparent greater perceptual strength of expanding motion is opposite to what we expected based on the direction of the anisotropy in postural sway, and it is also opposite to the results of previous studies reporting a lower threshold for contracting than for expanding optic flow (Edwards & Badcock, 1993;Edwards & Ibbotson, 2007).…”
Section: Postural Swaymentioning
confidence: 99%